2020
DOI: 10.1111/vop.12840
|View full text |Cite
|
Sign up to set email alerts
|

Impact of diurnal variation, sex, tear collection method, and disease state on tear protein levels in dogs

Abstract: Objective To investigate the effects of various biological factors on total protein concentration (TPC) and serum albumin levels in canine tears. Animals studied 10 healthy beagles (5 female, 5 male) were used. Procedures Experiments were conducted on separate days, collecting tears with either capillary tubes or Schirmer strips, as follows: (i) Tear collection at 3 hours intervals (from 6 am to 12 am); and (ii) Tear collection before and 20 minutes following topical histamine application (1, 10, 375 mg/mL) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Ocular disease likely affects the flow rate captured by Schirmer strips (µL/min) due to changes in tear film dynamics (tear volume, turnover rate), but the impact on VA and VR is likely minimal (to absent) as long as the mm‐mark wetness is kept constant (eg, same VA whether 20‐mm is reached within 40 s or 70 s). As for TPC, a recent study showed that Schirmer strips may actually be superior to capillary glass tubes for tear collection in inflamed eyes 5 . In fact, disease state did not exacerbate differences between Schirmer strips and capillary tubes in canine eyes, in contrast to the speculation that Schirmer strips might capture larger protein amounts by causing micro‐trauma to the hyperemic and more vulnerable conjunctiva 5 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ocular disease likely affects the flow rate captured by Schirmer strips (µL/min) due to changes in tear film dynamics (tear volume, turnover rate), but the impact on VA and VR is likely minimal (to absent) as long as the mm‐mark wetness is kept constant (eg, same VA whether 20‐mm is reached within 40 s or 70 s). As for TPC, a recent study showed that Schirmer strips may actually be superior to capillary glass tubes for tear collection in inflamed eyes 5 . In fact, disease state did not exacerbate differences between Schirmer strips and capillary tubes in canine eyes, in contrast to the speculation that Schirmer strips might capture larger protein amounts by causing micro‐trauma to the hyperemic and more vulnerable conjunctiva 5 …”
Section: Discussionmentioning
confidence: 99%
“…As for TPC, a recent study showed that Schirmer strips may actually be superior to capillary glass tubes for tear collection in inflamed eyes 5 . In fact, disease state did not exacerbate differences between Schirmer strips and capillary tubes in canine eyes, in contrast to the speculation that Schirmer strips might capture larger protein amounts by causing micro‐trauma to the hyperemic and more vulnerable conjunctiva 5 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accounting for a 2-fold dilution from mixing 1:1 with bacterial broth (see section Antimicrobial Susceptibility Testing), these 10 solutions provided albumin concentrations (0, 0.01, 0.05, 0.1, 0.2, 0.35, 0.5, 0.75, and 1, 2%) that represent a spectrum of albumin detected in tears of healthy canine eyes (generally ≤0.1%) and canine eyes with mild to severe conjunctival inflammation (generally 0.1–2%). This information was based on two previous reports ( 8 , 10 ) as well as prospective evaluation of 25 canine patients diagnosed with ulcerative keratitis at the Iowa State University's Lloyd Veterinary Medical Center, collecting and analyzing tear samples for albumin content as previously described ( 10 ). Briefly, tear collection was performed with dye-free Schirmer strips (Eye Care Product Manufacturing, Tucson, AZ) wetted until 20-mm mark, followed by centrifugation in pre-punctured 0.2-mL tubes at 3,884 g for 2 min and albumin quantification with a canine-specific ELISA kit (Serum albumin ELISA kit, Life Span Biosciences, Inc., Seattle, WA) following the manufacturer's guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…A large volume of tears (18 mL) was collected from dogs with ocular surface inflammation to provide biological fluid for the subsequent in vitro experiments. First, conjunctivitis was induced in both eyes with topical administration of 1% histamine solution, as previously described ( 8 , 10 ). Twenty minutes were allowed to pass for conjunctivitis to fully develop and ocular surface homeostasis to be restored ( 8 , 15 ).…”
Section: Methodsmentioning
confidence: 99%